Dane z monitoringu jako źródło dowodowe w postępowaniu kontrolnym państwowego inspektora pracy - Paroń, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Recent technological progress leads to changes in many areas of human life. Employers use increasingly refined methods to monitor the work performed by their employees. The reasons for such actions are understandable, and they have been approved by the legislator. However, the law permits video surveillance in specific cases and provided that specific requirements are met. The data collected during video surveillance of work are highly useful for employers. It seems, though, that the same data may also be of significant use for state labour inspectors as they check compliance with the labour law. This is because such data makes it possible to objectively establish the facts and the substantive truth. This article attempts to answer the questions related to the acceptability of using video surveillance evidence in inspections carried out by state labour inspectors.
Keywords: inspection of the state labour inspectorate; evidence procedure of a state labour inspector